Analisis perhitungan harga pokok produksi dalam penentuan harga jual pada Reidy Bakery di Desa Pangu Dua Kabupaten Minahasa Tenggara - Kojo, Melki Josenli; Pusung, Rudy J.; Mintalangi, Syermi S. E. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Reidy Bakery is the leading producer of bread and doughnuts. The company still uses a simple method to determine the cost of production. This study set out to determine the calculation of the cost of production and how this affects the selling price at Reidy Bakery. The method used is a descriptive method with a qualitative approach. We collected data through observation and interviews. The results clearly showed that Reidy Bakery included indirect labour costs in its calculation of production costs. The full costing method is the only way to calculate the cost of production. It includes all costs involved in the production process. The variable costing method does not include fixed factory overhead costs. Reidy Bakery should use both the full costing method and the variable costing method to determine the cost of production. The full costing method calculates all costs involved in the production process, providing an accurate overview of actual costs. The variable costing method is ideal for short-term decision-making, such as when fulfilling special orders or orders in large quantities, as it focuses on costs that change with production volume.